Study of some families of test functions via GFEM for the solution of one-dimensional convection-diffusion - Romão, Estaner Claro; Martins, Jairo Aparecido; Rizziolli, Eliris Cristina [UNESP] (Hikari, 2014)
This paper aims to present the formulation as of Finite Element Method, carried out via Weighted Residuals Method, for the solution of convection-diffusion problems. This work peculiarity is the usage of three types of test functions, polynomial and trigonometry functions (easily found in open literature) and, in special, with the application of hyperbolic functions. From the exact solutions taken as of the cases analyzed, each solution proposed has its efficiency demonstrated soon afterwards.
Keywords: Finite element method; Galerkin method; Hyperbolic functions; Polynomial functions; Trigonometric functions